The Effect of E-commerce Innovation and E-service Quality on Customer Loyalty with Customer Satisfaction as A Mediation for Shopee User in Soloraya - Shania Puspita Devi; Muhammad Amir Anshori (Manunggal Halim Jaya, 2026)
This study aims to examine the influence of e-commerce innovation and e-service quality on customer loyalty, with customer satisfaction as an intermediary or mediating variable for users of the Shopee application platform in Soloraya. The increasing competition between e-commerce platform requires companies to continue to innovate and improve the quality of digital service to maintain customer loyalty. This study uses a quantitative approach. The population of this study is all shopee users in Soloraya with an unknown number of samples, so the sample determination uses the Cochran formula. The sampling technique was carried out using a purposive sampling method on active shopee users, with a total of 334 respondents. Primary data was collected through an online questionnaire using a five-point likert scale. PLS-SEM was used to analyse data with SmartPLS 3.0 software. The research findings illustrate that e-commerce innovation and e-service quality have a positive or significant impact and influence on customer satisfaction and customer loyalty. In addition, customer satisfaction is proven to have a positive and significat effect on customer loyalty. The result of the mediation test indicate that customer satisfaction acts a a paryial mediator in the relationship between e-commerce innovation and e-service quality on customer loyalty. This finding confirms that platform innovation and optimally managed digital service quality play a significant role in increasing satisfaction and building sustainable loyalty among shopee users.